2024
DOI: 10.1111/tpj.16642
|View full text |Cite
|
Sign up to set email alerts
|

Specific ABA‐independent tomato transcriptome reprogramming under abiotic stress combination

Miriam Pardo‐Hernández,
Vicent Arbona,
Inmaculada Simón
et al.

Abstract: SUMMARYCrops often have to face several abiotic stresses simultaneously, and under these conditions, the plant's response significantly differs from that observed under a single stress. However, up to the present, most of the molecular markers identified for increasing plant stress tolerance have been characterized under single abiotic stresses, which explains the unexpected results found when plants are tested under real field conditions. One important regulator of the plant's responses to abiotic stresses is… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 99 publications
2
5
0
Order By: Relevance
“…Romero et al (2012) demonstrated that the application of ABA in sweet orange plant fruits from ABA-deficient mutant plants under dehydration condition did not produce a recovery at the transcriptomic level with respect to WT, supporting the results found in these experiments (Romero et al ., 2012). This was observed with 903 DEGs compared to WT under control conditions and it was also noted in a previous work of our group (Pardo-Hernández et al ., 2024). On the other hand, a certain number of DEGs were treatment-specific, obtaining 117, 567, 774 and 1426 DEGs specifically regulated under control, salinity, heat and stress combination respectively.…”
Section: Resultssupporting
confidence: 88%
See 3 more Smart Citations
“…Romero et al (2012) demonstrated that the application of ABA in sweet orange plant fruits from ABA-deficient mutant plants under dehydration condition did not produce a recovery at the transcriptomic level with respect to WT, supporting the results found in these experiments (Romero et al ., 2012). This was observed with 903 DEGs compared to WT under control conditions and it was also noted in a previous work of our group (Pardo-Hernández et al ., 2024). On the other hand, a certain number of DEGs were treatment-specific, obtaining 117, 567, 774 and 1426 DEGs specifically regulated under control, salinity, heat and stress combination respectively.…”
Section: Resultssupporting
confidence: 88%
“…Our research group has been demonstrating for more than a decade that the combination of abiotic stresses produces a specific response in plants that cannot be deduced from the application of the stresses separately. In addition, we have recently demonstrated that, although ABA is an essential hormone in these stress responses, there are certain genetic markers that are regulated independently of ABA and some of them are specific to the combination of salinity and heat (Pardo-Hernández et al ., 2024). Thus, this work was designed to further investigate the relationship between ABA and the possible coordination of the stress responses of tomato plants at different levels: phenomics, ionomics, transcriptomics, and metabolomics.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although ABA signaling results in a global change of gene expression (Rock 2000), the hormone does not affect the expression of genes involved in the response to ABA itself (for example, see (Pardo-Hernández et al 2024)). We thus treated seedlings with ABA and assayed the effect on AtPUB41 expression.…”
Section: Aba Induces the Expression Of Atpub41mentioning
confidence: 99%